PENYULUHAN PERLINDUNGAN KONSUMEN MENGENAI TUGAS DAN WEWENANG BADAN PENYELESAIAN SENGKETA KONSUMEN (BPSK), KRITERIA PRODUK HALAL, DAN STANDARDISASI MUTU BARANG GUNA MENCIPTAKAN KONSUMEN CERDAS DI KABUPATEN BUNGO - Yudhi Novriansyah; Muhammad Asman; Isman Isman (Jurnal Akrab Juara, 2018)
So far, people as users of goods and services often suffer losses both physically, morally and materially. Caused by the actions of Business Actors (PU) who commit fraud (fraud). The presence of the Consumer Dispute Settlement Agency (BPSK) is a fruit of reform with the birth of Law No. 8 of 199 concerning Consumer Protection (UUPK). BPSK is the institution for resolving disputes about consumer demands on their rights. Another obstacle that often occurs is the low public awareness of choosing products that are categorized as authentic / original halal by competent parties such as the Indonesian Ulema Council (MUI). We know that Islamic religion encourages people to use halal products and stay away from non-halal products which has been stated in Law No. 33 of 2014 concerning Guaranteed Halal Products. Then in the era of free trade, technical regulations relating to the circulation of goods and / or services imposed by a country must refer to and meet international standards. By meeting standards, local products are expected to be able to penetrate foreign markets with a higher level of competitiveness. In addition, the fulfillment of standards can also benefit consumers in terms of quality, competitive price of goods, and security of the use of goods that have met the Indonesian National Standard (SNI). The purpose of this Community Service is to provide understanding to the people of Bungo District, especially among the younger generation (students / students) so that in the future be smart consumers in the face of increasing consumerism turmoil and invasion of foreign products in the world free market era and ASEAN economic community (MEA).